2009
DOI: 10.1590/s0103-64402009000100014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of intermaxillary relationships of manual and swallowing methods

Abstract: This study compared the mandibular displacement from three methods of centric relation record using an anterior jig associated with (A) chin point guidance, (B) swallowing (control group) and (C) bimanual manipulation. Ten patients aged 25-39 years were selected if they met the following inclusion criteria: complete dentition (up to the second molars), Angle class I and absence of signs and symptoms of temporomandibular disorders and diagnostic casts showing stability in the maximum intercuspation (MI) positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 15 publications
2
13
0
4
Order By: Relevance
“…These techniques positioned the condyles more inferiorly and posteriorly relative to the condylar positions obtained from the Roth Power Bite and Leaf Gauge Techniques. Alverez et al, [21] also found no difference between condylar locations produced by the Chin Point Guidance and Bimanual Manipulation Techniques in the anterior-posterior dimension. Kantor et al, [11] likewise, found that the Chin Point Guidance and Bimanual Manipulation Techniques created the most similar mandibular displacement when compared with a swallowing technique and Chin Point Guidance with an anterior jig.…”
Section: Discussionmentioning
confidence: 92%
“…These techniques positioned the condyles more inferiorly and posteriorly relative to the condylar positions obtained from the Roth Power Bite and Leaf Gauge Techniques. Alverez et al, [21] also found no difference between condylar locations produced by the Chin Point Guidance and Bimanual Manipulation Techniques in the anterior-posterior dimension. Kantor et al, [11] likewise, found that the Chin Point Guidance and Bimanual Manipulation Techniques created the most similar mandibular displacement when compared with a swallowing technique and Chin Point Guidance with an anterior jig.…”
Section: Discussionmentioning
confidence: 92%
“…The choice for the frontal manipulation technique designed by Ramfjord and Ash (1983) is attributed to its high reproducibility and applicability among the record-guided techniques when used gently It is used only to guide the patient properly relaxed while searching for a comfortable CR position, making a hypothetical clockwise condylar displacement (15,24).…”
Section: Discussionmentioning
confidence: 99%
“…Należy jednak pamiętać, że wielkość położenia spoczynkowego żuchwy zależy od wielu czynników, takich jak: postawa ciała, pozycja żuchwy, napięcie psychoemocjonalne. [30][31][32][33][34][35][36] Z tego powodu, w celu określenia wysokości zwarcia stosowane są dodatkowe metody postępowania (analiza telerentgenogramów bocznych głowy, aksjografia, kinezjografia). 6,37-44 Na podstawie telerentgenogramów bocznych głowy oblicza się wysokość dolnego odcinka twarzy.…”
Section: Deprogramacja Mięśniunclassified
“…32,37 Druga metoda wykorzystuje odruch połykania, kiedy w końcowej fazie przełykania śliny żu-chwa ustawia się w pożądanej, najbardziej dotylnej, ale niewymuszonej pozycji. [33][34][35][36] Ustalanie relacji centralnej można opierać na stosowaniu zarówno czynnych, jak i biernych metod postępowania. Położenie żuchwy w relacji centralnej można uzyskać bez specjalistycznej aparatury, wykorzystując pracę mięśni żucia i więzadeł, co potwierdzają badania przeprowadzone przez McKee.…”
Section: Deprogramacja Mięśniunclassified